Dissolved Gas Analysis (DGA) of canola-based ester fluid - Mnisi, Hlengiwe (My University, 2021)
This dissertation presents the investigation of the Dissolved Gas Analysis (DGA) of canola-based ester fluid when subjected to a high energy discharge fault. Recently, ester fluids have been introduced to transformers to replace the widely used mineral oil due to better fire safety and biodegradability characteristics of the organic insulating fluids. The introduction of ester fluids in power transformers raises the need for investigating the DGA of ester fluid given the difference in the chemical structure of ester fluid with mineral oil. The high energy discharge in the canola-based ester fluid was generated by the application of an A.C voltage sufficient to cause continuous break down across an electrode gap for 15 seconds. The resulting dissolved gases reveal that the even though, the type of gases dissolved in the canola-based ester fluid are similar to those in mineral oil, the quantities of the dissolved hydrocarbon gases are lower in the ester fluid. Also, the ester fluid generates higher amounts of carbon oxides, and additional ethane. An evaluation of the traditional DGA interpretation methods revealed that the IEC 60599 ratios, Roger’s ratios and the newly developed Duval’s triangle three (BIOTEMP and FR3) can in average correctly identify the high energy discharge in the canola-based ester fluid. However, the IEEE key gas method requires modification to accommodate the production carbon oxides produced in the canola-based ester fluid. For future work, it is recommended that higher voltages in the range of in-service transformers are used for the high energy discharge. This is to ensure that all effect that could results in actual service transformers are fully studied. Also the work is recommended to be extended to other various types of ester fluids.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2021